The Functional Beginning of Belligerent Occupation - Michael Siegrist (Graduate Institute Publications, 2011)
Since the mid-19th century military powers and various writers have tried to define the notion of belligerent occupation and, in particular, the beginning thereof. There are many situations in which a state of occupation is controversial or even denied. When is control so effective that an invasion turns into a state of belligerent occupation? What is the minimum area of a territory that can be occupied; a town, a hamlet, a house or what about a hill taken by the armed forces? This paper exam...